Pembinaan Membaca Alkitab Dengan Baik Di SDN Inpres No 318 Padakka, Lembang Maroson, Kecamatan Kurra, Kabupaten Tana Toraja - Sumiaty, Sumiaty (IAKN TORAJA, 2022)
Abstract: The purpose of this community service is to foster students of SDN Inpres No. 318 Padakka in reading the Bible well. The type of research in this service is Classroom Action Research (CAR) with a qualitative approach. This research was conducted at SDN Inpres No. 318 Padakka, Lembang Maroson. The subjects of this study were students of class V and VI with a total of 20 students. The methods are lecture, practice, and question and answer. Giving material content by explaining PUEBI, especially on the use of punctuation marks, explaining PUEBI material at the beginning of the activity is a strategy so that students can understand the use of punctuation well. Besides that, teaching aids such as Bible picture stories are also used so that students are more interested in reading the Bible. The research action design was carried out through 1 cycle in which there were four stages in the cycle, namely: a) observation, b) preparation of materials and teaching materials, c) implementation of activities, and d) monitoring. The result of the implementation of this coaching is that students are able to provide good responses, taking into account the material provided by the service team. Students can practice how to read the Bible well according to the explanations from the service team. The students are very enthusiastic about participating in the coaching, it can be seen when students play an active role in the coaching process. The success of this coaching is due to the ability of the service team in delivering and making interesting material so that students don't get bored. Abstrak: Tujuan pengabdian masyarakat ini adalah untuk membina siswa SDN Inpres No 318 Padakka dalam membaca Alkitab dengan baik. Jenis penelitian pada pengabdian ini adalah Penelitian Tindakan Kelas (PTK) dengan pendekatan kualitatif. Penelitian ini dilaksanakan di SDN Inpres No 318 Padakka, Lembang Maroson. Subjek penelitian ini adalah siswa kelas V dan VI dengan jumlah 20 siswa. Adapun metodenya yaitu ceramah, praktik, dan tanya jawab. Pemberian muatan materi dengan menjelaskan PUEBI khususnya pada penggunaan tanda baca, penjelasan materi PUEBI pada awal kegiatan merupakan strategi agar siswa dapat memahami penggunaan tanda baca dengan baik. Selain itu digunakan juga alat peraga seperti cerita bergambar Alkitab agar siswa lebih tertarik lagi dalam membaca Alkitab. Rancangan tindakan penelitian dilakukan melalui 1 siklus di mana pada siklus tersebut terdapat empat tahap yaitu: a) observasi, b) persiapan materi dan bahan ajar, c) pelaksanaan kegiatan, dan d) monitoring. Hasil pelaksanaan pembinaan ini adalah siswa mampu memberikan tanggapan yang baik, dengan memperhatikan materi yang diberikan oleh tim pengabdi. Siswa dapat mempraktikkan cara membaca Alkitab dengan baik sesuai dengan penjelasan dari para tim pengabdi. Para siswa sangat antusias mengikuti pembinaan, hal itu dapat dilihat saat siswa berperan aktif dalam proses pembinaan. Keberhasilan pembinaan ini tidak lain berkat kemampuan yang dimiliki oleh tim pengabdi dalam penyampaian dan pembuatan materi yang menarik sehingga para siswa tidak bosan.